The Impact of Pandemic Perception, National Feeling, and Media Use on the Evaluation of the Performance of Different Countries in Controlling COVID-19 by Chinese Residents - Han, Ruixia; Xu, Jian (Frontiers in Psychology, 2021)
Different nations responded to the global spread of Covid-19 differently. how do people view the governance practices and effects of various countries? What factors affect their views? Starting from the three-dimensional model of cognitive-affective-media, this study examines how pandemic perception, national feeling which is the public's emotional preference for different countries and media use affect the Chinese public's views on the performance of other countries in controlling Covid-19. After regression analysis on the data of 619 Chinese public samples collected by an online survey, it reveals that: (1) pandemic perception is negatively correlated with Chinese residents’ evaluation of controlling-pandemic performance in different countries, and national feeling is positively correlated with evaluation of controlling-pandemic performance. (2)The use of media has different characteristics in Chinese residents’ evaluation of the controlling-pandemic performance of different countries. Television has a significant influence on Chinese residents’ evaluations of the United States, China and Germany. (3) Collectivist cultural orientation has no significant impact on Chinese residents’ evaluation of the anti-pandemic performance of different countries, and virus perception only has a significant impact on the evaluation of the anti-pandemic performance of the United States and Italy. Research has confirmed the existence of cognitive-affective-media model in public’s evaluations on other countries governance, and prospects for the superimposed role of media in cognitive-affective model.